Factors that improve probation officers impact for Māori on probation supervision : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Manawatu, New Zealand - Barrett, Victoria (Massey University, 2024)
The disproportionate number of Māori involved in the justice system is deeply concerning. Māori account for 17% of the total population yet comprise 40% of police arrests and 53.2% of the correctional population in Aotearoa (New Zealand). (The Department of Corrections, Dec 2022). Re-conviction rates for Māori are significantly higher than other ethnicities on average, Māori accumulate 5 to 6 community sentences prior to entering prison, suggesting it is sensible to focus on what works to prevent Māori incarceration. Notwithstanding systemic issues associated with these statistics, research has shown that Probation Officers and the probation process have the potential to positively impact the people serving sentences. This thesis proposes to gain a more holistic understanding of Probation Officers and supervision practices that improve outcomes for Māori within the Aotearoa justice system. Ten Probation Officers and four Māori on probation supervision were interviewed using key themes identified in a literature review. Probation Officers were also asked to complete a personality assessment, which was used to validate some of the findings regarding interpersonal skills. Results suggest a range of multifaceted and complex factors interact and ultimately result in the likelihood of breaking the cycle of criminal behaviour. Further analysis revealed the majority of themes aligned with the Meihana Model, an Indigenous cultural competence framework designed to provide a practical approach to delivering culturally safe practices for Māori and their families. The implications of these findings are discussed in relation to improving transformational outcomes for Māori within the justice system.
Keywords: Māori Masters Thesis; 440202 Correctional theory, offender treatment and rehabilitation; 451017 Te oranga ā-pāpori, ā-hinengaro, ā-ahurea, ā-wairua o te Māori (Māori social, cultural, emotional and spiritual wellbeing)